Advances in Hyaluronic Acid for Biomedical Applications - Yasin, Aqeela; Ren, Ying; Li, Jingan; Sheng, Yulong; Cao, Chang; Zhang, Kun (Frontiers in Bioengineering and Biotechnology, 2022)
Hyaluronic acid (HA) is a large non sulphated glycosaminoglycan that is a main component of extracellular matrix (ECM). Due to its strong and diversified functions applied in broad fields, HA has been widely studied and reported previously. The molecular properties of HA and its derivatives, including wide range of molecular weight but distinct effects on cells, moisture retention and anti-aging, CD44 targeting, promised its role as a popular participant on tissue engineering, wound healing, cancer treatment, ophthalmology and cosmetics. In recent years, HA and its derivatives, have played an increasingly important role in the above biomedical fields in the formulation of coatings, nanoparticles and hydrogels. This review highlights recent efforts in in converting the HA to smart formulation, such as multi-functional coatings, targeted nanoparticles or injectable hydrogels, which are used to the advanced biomedical application.